Description of two new species of Lysmata Risso, 1816 (Decapoda, Lysmatidae) from the China seas, with remarks on Lysmata vittata (Stimpson 1860) - Wang, Yan-Rong; Sha, Zhong-Li (Zootaxa, 2018)
Two new species of Lysmata Risso, 1816 are described and illustrated from the China seas. L. brevrostrus sp. nov. is characterized by the short rostrum not reaching the distal margin of the eyes, and the rostral ventral margin unarmed with tooth; L. parvispinosus sp. nov. is characterized by the dactylus of posterior three pereiopods tapering (not biunguiculate) and the flexor margin of the dactylus bearing two basal inconspicuous spinules. A morphologically variable species, L. vittata (Stimpson 1860), is discussed based on specimens collected from the China seas.